Digital Financial Transactions Using QRIS Reviewed From The Legal Aspects - Wongsowinoto, Fridayani; CUACA, BENNY (Inovbiz: Jurnal Inovasi Bisnis, 2024)
One sector that is experiencing changes in the current digital era is the financial sector, where payment transactions are starting to be carried out through digital systems, some of which use the QRIS system. Payment transactions via QRIS can speed up transactions and reduce operational costs, especially for commercial players. However, the use of QRIS has clearly given rise to what is called digital crime, which can harm users (QRIS consumers) by destroying the QR code and "undoing" the actions carried out by the perpetrator. This research uses qualitative research with data collection techniques through library research which is analyzed qualitatively. The results of the first research concluded that legal protection for QRIS users based on current regulations includes PJSP having valid legal status, PJSP must create a financial innovation ecosystem with good digital credentials in the financial services sector and be registered with the Financial Services Authority. OJK and QRIS users (consumers) enjoy rights based on the provisions of the Consumer Protection Law and the ITE Law. Second, the legal consequences of misusing consumer data in digital transactions using QRIS make the perpetrator liable for professional misconduct. For losses incurred, QRIS users can file a civil lawsuit or compensation through PJSP, as stipulated in Article 12, paragraph 1, Law no. 27, 2022 on personal data protection.